1D Langat river modelling by using unsteady flow hec ras - Muhammad Akmal Arief, Abdul Jabbar (2014)
Malaysia is one of the countries that place in the equator of the Earth and face a tropical weather which contain rainy and drought seasons. Nowadays, there are a lot of flood occur near the middle Sungai Langat, Selangor which effects the society. Due to the phenomena of the flood disaster, there are a lot of lost and this situation will affect the economics of the people that live around this area. This scenario can be predicted and can be analyse by using Hydrologic Engineering Centers Rivers Analysis System (HEC RAS). HEC RAS is one of the software that has been produce by U.S Army Corps of Engineers which allows the user to perform 1 dimensional steady and unsteady flow rivers hydraulic calculations. The data collections contain cross section data, rainfall data and the discharge data. All the data will be interpret in the HEC RAS and the river modelling can be produce on it. The dimension of the river can be produce by the AUTOCAD based on the data that had been collected. The results of this research are focus only for 10 years, 50 years and 100 years return period. Based on the research, actually the channel of the river, is safe during 10 years and 50 years return period but during 100 years, the river channel cannot withstand the capacity of the river. Due to this problem, the river normalization had been selected as the way to solve the problem.The focus study of this research is about the river capacity analysis, river normalization and hydraulic variable difference (river discharge, depth of water, etc) of the flow after and before the normalization.